2002
DOI: 10.1016/s0092-8674(02)01005-x
|View full text |Cite
|
Sign up to set email alerts
|

Function and Selectivity of Bromodomains in Anchoring Chromatin-Modifying Complexes to Promoter Nucleosomes

Abstract: The functions of the SAGA and SWI/SNF complexes are interrelated and can form stable "epigenetic marks" on promoters in vivo. Here we show that stable promoter occupancy by SWI/SNF and SAGA in the absence of transcription activators requires the bromodomains of the Swi2/Snf2 and Gcn5 subunits, respectively, and nucleosome acetylation. This acetylation can be brought about by either the SAGA or NuA4 HAT complexes. The bromodomain in the Spt7 subunit of SAGA is dispensable for this activity but will anchor SAGA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
396
3
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 490 publications
(434 citation statements)
references
References 49 publications
31
396
3
4
Order By: Relevance
“…Brahma of the SWI2/ SNF2 family of the ATP-dependent remodeling enzymes contains a bromodomain, which binds acetylated histones (Hassan et al, 2002). Similar domain conservation was observed for E. heros (Figure 1A).…”
Section: Domain Conservation In Chromatin Remodeling Atpases Of D Vsupporting
confidence: 66%
“…Brahma of the SWI2/ SNF2 family of the ATP-dependent remodeling enzymes contains a bromodomain, which binds acetylated histones (Hassan et al, 2002). Similar domain conservation was observed for E. heros (Figure 1A).…”
Section: Domain Conservation In Chromatin Remodeling Atpases Of D Vsupporting
confidence: 66%
“…Histone modifications were however found to effect the interaction of SWI/SNF with nucleosomes. Acetylation by SAGA and NuA4 was found to stabilize SWI/ SNF interaction with nucleosome in a bromodomain dependent manner [49,145]. Acetylation of lysine 8 of histone H4 has also been shown to facilitate recruitment of SWI/SNF [146].…”
Section: Role Of Histone Tails and Their Modification In Chromatin Rementioning
confidence: 98%
“…The ATPase domain consists of seven subdomains that structurally forms two lobes referred to as the DEXD and helicase motifs that form a cleft to which DNA binds based on X-ray crystal structure from the related Rad54 ATPase domain [41,42]. In addition the Swi2/Snf2 protein contains at its Cterminus a bromo domain which has been shown to recognize specific acetylated lysines in histone tails [43][44][45][46][47][48][49][50]. The Swi1 contains an ARID domain (an AT-rich interaction domain) that is found in its orthologs OSA in Drosophila and BAF250 in mammals.…”
Section: Nucleosome Remodeling Complexes Swi/snf Familymentioning
confidence: 99%
“…Studies in different eukaryotes have suggested that the presence of SAGA at the promoters of genes is needed to facilitate Pol II recruitment and pre‐initiation complex (PIC) formation (Wyce et al , 2007; Nagy et al , 2009; Helmlinger et al , 2011; Lang et al , 2011). The recruitment of SAGA and ATAC coactivator complexes to genomic loci has been suggested to take place by several distinct mechanisms: (i) by activator mediated recruitment (McMahon et al , 1998; Brown et al , 2001; Fishburn et al , 2005; Reeves & Hahn, 2005), (ii) by interactions with basal transcription machinery components (Larschan & Winston, 2001; Laprade et al , 2007; Mohibullah & Hahn, 2008) and (iii) through chromatin‐interacting domains of SAGA and ATAC subunits (Hassan et al , 2002; Vermeulen et al , 2010; Bian et al , 2011; Bonnet et al , 2014). Nevertheless, the dynamics of SAGA and ATAC interactions with chromatin are not yet well understood, as there has been no direct and systematic monitoring of the nuclear mobility of these two co‐activator complexes in live cells.…”
Section: Introductionmentioning
confidence: 99%